Photocatalytic degradation of phenol in a fluidized bed reactor utilizing immobilized TiO2 photocatalyst: Characterization and process studies - Zulfakar, Mokhtar; Hairul Nazirah, Abdul Halim; Akmal Hadi, Ma'Radzi; Abdul Rahman, Mohamed, Prof. Dr. (Asian Network for Scientific Information, 2011)
Link to publisher's homepage at http://www.ansinet.com/